A coupled thermal-drop impact analysis-based safety assessment of radioactive material cask. Issue 2 (9th April 2018) - Liu, Qiang; Zhu, Shun-Peng; Yu, Zheng-Yong; Ding, Ran
Abstract : Purpose: Transport is an integral part of the nuclear fuel cycle. The procedures employed are designed and conducted to ensure the public and environment protection both routinely and when transport accidents occur. According to this, the purpose of this paper is to focus on a coupled thermal-drop impact analysis-based safety assessment of a nuclear fuel cask. Design/methodology/approach: For the cask, high altitude falling and fire accidents are the two most serious accidents during its transportation. In this paper, a sequentially coupled thermal-drop impact analysis is performed by using a nuclear fuel cask model for safety assessment. High altitude falling and fire accidents of the nuclear fuel cask were conducted by using finite element simulations for coupled thermal-drop impact analysis. Findings: Results showed that the cask can withstand a drop test and survive a fire of 800°C for 30 minutes. In addition, an improved design is explored and evaluated, which provides a reference for structural design and safety assessment of nuclear fuel casks. Originality/value: A coupled thermal-drop impact analysis-based safety assessment procedure is developed for the nuclear fuel cask.